KEBIJAKAN KRIMINAL DALAM PENANGGULANGAN PENYELUNDUPAN MANUSIA DI INDONESIA - Evlyn Martha Julianthy, Dahlan Ali, Mujibussalim. (Jurnal Ilmu Hukum, 2014)
Abstract: Human smuggling is a transnational organized crime and negatively impacts numerous countries, particularly Indonesia as a transit country. In addition, it should be distinguished from human trafficking. Human smuggling in Indonesia continues to increase significantly and should be addressed. Criminal policies on the mitigation of human smuggling in Indonesia are performed by using the penal policy and non-penal facilities. The penal policies are the amendment of immigration laws that criminalize human smuggling, and as the formulation of criminal sanctions towards the perpetrators of human smuggling. In addition, there are also expansion policies of the authority of civil servant investigators (PPNS) in the immigration in dealing with human smuggling, and the application of non-refoulement principles for the victims of human smuggling. The criminal policies with non-penal facilities in the mitigation of human smuggling in Indonesia are done by cooperating with other countries, conducting legal counseling to coastal communities, establishing coast guard by using radar system capable of covering the entire territory of Indonesia, improving the quality of law enforcement agencies in mitigating human smuggling in Indonesia, and increasing the budget to support the mitigation and prevention of human smuggling. Keywords: Criminal policy, mitigation, human smuggling. Abstrak: Penyelundupan manusia merupakan kejahatan transnasional terorganisir dan telah membawa dampak negatif pada berbagai negara khususnya Indonesia sebagai negara transit. Penyelundupan manusia harus dibedakan dengan perdagangan orang. Penyelundupan manusia merupakan isu kemanusiaan di samping isu migrasi, dan masih terus terjadi di Indonesia sehingga dibutuhkan suatu upaya yang rasional untuk menanggulangi kejahatan penyelundupan manusia di Indonesia, atau yang dikenal dengan istilah kebijakan kriminal (criminal policy). Kebijakan kriminal dalam menanggulangi penyelundupan manusia dengan menggunakan hukum pidana yakni pembaruan undang-undang keimigrasian yang memuat kriminalisasi terhadap penyelundupan manusia serta rumusan sanksi pidana terhadap pelaku penyelundupan manusia. Selain itu juga terdapat kebijakan perluasan kewenangan Penyidik Pegawai Negeri Sipil (PPNS) Keimigrasian dalam menangani penyelundupan manusia, serta penerapan prinsip non-refoulement bagi korban penyelundupan manusia. Kebijakan kriminal dengan sarana non penal dalam penanggulangan penyelundupan manusia di Indonesia dilakukan dengan cara mengadakan kerjasama dengan negara lain, mengadakan penyuluhan hukum kepada masyarakat pesisir, membentuk penjaga pantai dengan sistem radar yang mampu menjangkau seluruh wilayah Indonesia, peningkatan kualitas aparat penegak hukum dalam menanggulangi penyelundupan manusia di Indonesia, serta peningkatan anggaran untuk menunjang penanggulangan dan pencegahan penyelundupan manusia. Kata Kunci : Kebijakan kriminal, penanggulangan, penyelundupan manusia.